All-vanadium liquid flow battery felt and its preparation process

By using nitrogen-containing phosphorus-containing polyacrylonitrile copolymer to coat perovskite metal oxides and dopamine boron system adhesion technology in all vanadium flow batteries, the problem of poor stability of perovskite metal oxides on carbon fiber surface is solved. , improves electrochemical activity and battery performance, and enhances the reactivity and hydrophilicity of the electrode.

CN118782813BActive Publication Date: 2024-12-20沈阳富莱碳纤维有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411239260.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-20
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

Perovskite metal oxides are difficult to exist on the carbon fiber surface for a long time, resulting in insufficient electrochemical activity of all vanadium flow batteries and poor hydrophilicity of graphite felts, which affects energy storage capacity and efficiency.

Method used

The perovskite metal oxide is coated with a polyacrylonitrile copolymer containing nitrogen and phosphorus, and adhered through a dopamine boron system to form a porous carbon fiber electrode, improving the vanadium redox reaction activity and electrochemical properties.

Benefits of technology

It effectively reduces the possibility of perovskite metal oxides leaving the fiber, improves electrochemical activity and battery performance, enhances the reactive activity and hydrophilicity of the electrodes, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of liquid flow battery energy storage materials, and more specifically, it relates to an all-vanadium liquid flow battery felt and its preparation process. An all-vanadium liquid flow battery felt, the all-vanadium liquid flow battery felt is prepared by pre-oxidation and carbonization of raw fiber of perovskite-type metal oxide coated with nitrogen-phosphorus polyacrylonitrile copolymer. The all-vanadium liquid flow battery felt of the present application has excellent electrochemical activity, and the perovskite-type metal oxide can exist on the surface of carbon fiber for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of liquid flow battery energy storage raw materials, and more specifically, it relates to an all-vanadium liquid flow battery felt and a preparation process thereof. Background Art

[0002] As one of the most promising large-scale energy storage technologies, the rated power and rated power of the all-vanadium flow battery can be designed individually. It can be instantly charged by replacing the electrolyte, and 100% deep discharge will not damage the battery. Based on the above advantages, it can be widely used in wind energy, solar energy and other energy storage, grid peak regulation, uninterruptible power supply and other aspects.

[0003] Graphite felt electrode is one of the most critical components in all-vanadium liquid flow batteries and is crucial to the energy storage capacity and efficiency of all-vanadium liquid flow batteries. However, its high degree of graphitization leads to poor hydrophilicity of graphite felt, insufficient active sites, and weak electrochemical activity for vanadium redox reactions.

[0004] At present, the modification of graphite felt electrode materials generally adopts transition metals and their oxides, such as perovskite metal oxides. However, perovskite metal oxides are difficult to exist on the surface of carbon fibers for a long time, and their electrochemical performance is unstable. Summary of the invention

[0005] In order to improve the defect that perovskite-type metal oxides are difficult to exist on the surface of carbon fibers for a long time, the present application provides an all-vanadium liquid flow battery felt and a preparation process thereof.

[0006] In a first aspect, the present application provides an all-vanadium liquid flow battery felt, which adopts the following technical solution:

[0007] The invention discloses an all-vanadium liquid flow battery felt, which is prepared by pre-oxidation and carbonization of raw silk fibers of perovskite-type metal oxide coated with nitrogen-phosphorus-containing polyacrylonitrile copolymer.

[0008] Since the perovskite metal oxide is coated inside the nitrogen-phosphorus-containing polyacrylonitrile copolymer, the possibility of the perovskite metal oxide detaching from the fiber is effectively reduced, thereby indirectly improving the electrochemical activity of the all-vanadium liquid flow battery felt.

[0009] In addition, the porous carbon fiber is doped with P and N, both of which are n-type doping of heteroatoms that can provide additional free electrons. N doping provides more coordination active sites for electrode reactions, reducing the activation energy of redox reactions, while P doping can form active and stable CP bonds and P-OH functional groups, which on the one hand enhance the reaction activity of the electrode surface, and on the other hand form a hierarchical pore structure with a high specific surface area, thereby improving battery performance. In addition, the introduction of P atoms can also promote the carbonization degree of N-doped carbon materials in high-temperature treatment to a certain extent.

[0010] Preferably, the nitrogen-phosphorus-containing polyacrylonitrile copolymer coated perovskite-type metal oxide comprises the following raw materials: pentaerythritol phosphate, 3-isopropenyl-α, α-dimethylbenzyl isocyanate, amidated perovskite-type metal oxide, dicyclohexylcarbodiimide, 2-(carboxymethylthio)benzoic acid and azobisisoheptonitrile.

[0011] Preferably, the method for preparing the nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with a perovskite-type metal oxide comprises the following steps:

[0012] S1. First, dispersing pentaerythritol phosphate in N, N-dimethylformamide, then adding 3-isopropenyl-α, α-dimethylbenzyl isocyanate, heating to react, and then precipitating, filtering and drying in deionized water to obtain a nitrogen-phosphorus intermediate;

[0013] S2, dispersing the amino perovskite metal oxide in N, N-dimethylformamide, and then adding dicyclohexylcarbodiimide and 2-(carboxymethylthio)benzoic acid, mixing and stirring evenly to obtain a perovskite metal oxide chain transfer agent;

[0014] S3, mixing 1,4-dioxane, a perovskite-type metal oxide chain transfer agent, azobisisoheptylnitrile, a nitrogen-phosphorus-containing intermediate and acrylonitrile to obtain a nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with a perovskite-type metal oxide.

[0015] In the synthesis, the hydroxyl group of pentaerythritol phosphate reacts with 3-isopropenyl-α,α-dimethylbenzyl isocyanate to obtain a phosphorus-nitrogen-containing vinyl monomer, and the amino perovskite-type metal oxide reacts with 2-(carboxymethylthio)benzoic acid through an amide reaction to synthesize a graft chain transfer agent. Under the initiation of azobisisoheptanenitrile, the phosphorus-nitrogen-containing vinyl monomer and acrylonitrile are polymerized on the surface of the perovskite-type metal oxide chain transfer agent, thereby completing the loading of phosphorus and nitrogen while also coating the perovskite-type metal oxide, causing the perovskite-type metal oxide to be coated inside the nitrogen-phosphorus polyacrylonitrile copolymer, thereby effectively reducing the possibility of the perovskite-type metal oxide detaching from the fiber, and indirectly improving the electrochemical activity of the all-vanadium liquid flow battery felt.

[0016] Preferably, in S1, the mass ratio of pentaerythritol phosphate to 3-isopropenyl-α, α-dimethylbenzyl isocyanate is (3-6): (10-14), the reaction temperature is 40-50° C., and the reaction time is 3-5 h;

[0017] and / or;

[0018] In S2, the mass ratio of the amide perovskite-type metal oxide, 2-(carboxymethylthio)benzoic acid and dicyclohexylcarbodiimide is 1:(1-3):(1-2), the reaction temperature is 20-30°C, and the reaction time is 20-30h;

[0019] and / or;

[0020] In S3, the mass ratio of the perovskite-type metal oxide chain transfer agent, azobisisoheptanenitrile, nitrogen-phosphorus intermediate and acrylonitrile is (0.2-0.5): (0.15-0.25): (0.5-0.8): (8-12), the reaction temperature is 40-60°C, and the reaction time is 10-20h.

[0021] Preferably, the amino perovskite-type metal oxide is a perovskite-type metal oxide modified with γ-aminopropyltriethoxysilane.

[0022] Preferably, the structural formula of the perovskite metal oxide is ABO3, A is one of Ca, Sr, and Ba, and B is one of Ti, Zr, and Hf.

[0023] Preferably, the perovskite metal oxide is SrZrO3.

[0024] SrZrO3 has relatively more oxygen defects, which promotes the adsorption of vanadium ions. At the same time, the Zr-O bond orbital hybridization is weak, which is beneficial to the charge transfer of the anode reaction. At the same time, SrZrO3 has good hydrophilicity, large surface area, excellent crystal structure and relatively moderate particle size, which ensures excellent catalytic activity.

[0025] Preferably, the preparation method of the amino perovskite metal oxide is: dissolving zirconium nitrate in deionized water, then adding strontium nitrate to dissolve completely, in the solution, the molar ratio of strontium to titanium is 1:1, and then adding citric acid as a complexing agent, the molar amount of citric acid is 1.5 times the molar amount of total metal ions, and then mixing and stirring at a temperature of 70-90°C to form a transparent sol, and then drying and grinding into powder, and then calcining at a temperature of 800-1000°C for 2-4h, and finally mixing and drying with 20wt% of the total mass of γ-aminopropyltriethoxysilane to obtain the amino perovskite metal oxide SrZrO3.

[0026] Preferably, a dopamine-boron system is attached to the surface of the precursor fiber of the nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with the perovskite-type metal oxide;

[0027] The attachment method of the dopamine boron system is:

[0028] First, the raw silk fibers coated with nitrogen and phosphorus-containing polyacrylonitrile copolymers of perovskite-type metal oxides are dried and immersed in Tris-HCl buffer, and dopamine monomer is added and stirred. The oxygen in the air is used as a catalyst to achieve dopamine self-polymerization and coating. The coated raw silk fibers are then immersed in a boric acid solution, and finally washed and dried to complete the attachment of the dopamine boron-boron system.

[0029] The attachment of the dopamine boron system promotes the simultaneous doping of boron on the surface of the carbon fiber, and boron can form pn-type co-doping with P and N. Specifically, pn co-doping is the co-doping of n-type atoms with lone pairs of electrons and p-type atoms with empty orbitals into the electrode, wherein N and P can introduce defects and vacancies in the carbon matrix, thereby serving as new active sites to accelerate the redox reaction of vanadium ions, and B can form transition bonds with vanadium ions, thereby promoting electron transfer between reactants and electrodes, and improving the hydrophilicity of the electrode while increasing active sites.

[0030] Preferably, the addition concentration of the dopamine monomer is 1-4 g / L, and the mass ratio of the nitrogen-phosphorus-containing polyacrylonitrile copolymer-coated perovskite-type metal oxide precursor fiber to dopamine is (2-5): (1-4).

[0031] Preferably, the concentration of the boric acid solution is 1-5 g / L, and the mass ratio of the nitrogen-phosphorus-containing polyacrylonitrile copolymer-coated perovskite-type metal oxide precursor fiber to boric acid is (2-5): (1-5).

[0032] In a second aspect, the present application provides a method for preparing an all-vanadium liquid flow battery felt, using the following technical solution:

[0033] A preparation process of all-vanadium liquid flow battery felt comprises the following steps:

[0034] Step 1: Prepare a nanofiber membrane by electrospinning a nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with a perovskite-type metal oxide. During the spinning process, the spinning solution flow rate is 0.5-1.0 ml / h, the receiving distance is 10-20 cm, the receiving end rotor speed is 500-800 rpm, the voltage between the needle and the receiving end is 20-40 kV, the temperature is 20-40 ° C, the relative humidity is 40-70%, and the nanofiber membrane thickness is 1-3 mm;

[0035] Step 2: Place the nanofiber membrane in the air for pre-oxidation, and then place it in an argon or nitrogen atmosphere for high-temperature carbonization to obtain an active porous carbon fiber electrode; the pre-oxidation temperature is 200-300°C, the heating rate is 2-8°C / min, the time is 1-3h, and the carbonization temperature is 800-3000°C, the heating rate is 4-10°C, and the time is 2-4h.

[0036] In summary, this application has the following beneficial effects:

[0037] 1. Since the perovskite metal oxide is coated inside the nitrogen-phosphorus-containing polyacrylonitrile copolymer, the possibility of the perovskite metal oxide detaching from the fiber is effectively reduced, and the electrochemical activity of the all-vanadium liquid flow battery felt is indirectly improved.

[0038] 2. The porous carbon fiber is also doped with P and N. Both P and N are n-type doping of heteroatoms that can provide additional free electrons. N doping provides more coordination active sites for electrode reactions and reduces the activation energy of redox reactions. P doping can form active and stable CP bonds and P-OH functional groups, which on the one hand enhance the reaction activity of the electrode surface, and on the other hand form a hierarchical pore structure with a high specific surface area, thereby improving battery performance. In addition, the introduction of P atoms can also promote the carbonization degree of N-doped carbon materials during high-temperature treatment to a certain extent.

[0039] 3. SrZrO3 has relatively more oxygen defects, which promotes the adsorption of vanadium ions. At the same time, the hybridization of Zr-O bond orbitals is weak, which is beneficial to the charge transfer of the anode reaction. At the same time, SrZrO3 has good hydrophilicity, large surface area, excellent crystal structure and relatively moderate particle size, which ensures excellent catalytic activity.

[0040] 4. The adhesion of dopamine boron system promotes the simultaneous doping of boron on the surface of carbon fiber, and boron can form pn-type co-doping with P and N. Specifically, pn co-doping is to co-dope n-type atoms with lone pair electrons and p-type atoms with empty orbitals in the electrode, wherein N and P can introduce defects and vacancies in the carbon matrix, and then serve as new active sites to accelerate the redox reaction of vanadium ions, while B can form transition bonds with vanadium ions, thereby promoting electron transfer between reactants and electrodes, and improving the hydrophilicity of the electrode while increasing active sites. DETAILED DESCRIPTION

[0041] The present application is further described in detail below in conjunction with Examples 1-8 and Comparative Examples 1-2.

[0042] raw material

[0043] Pentaerythritol phosphate CAS: 7440-78-0; 3-isopropenyl-α,α-dimethylbenzyl isocyanate CAS: 2094-99-7; dicyclohexylcarbodiimide CAS: 538-75-0; 2-(carboxymethylthio)benzoic acid CAS: 135-13-7; azobisisoheptonitrile CAS: 4419-11-8; N,N-dimethylformamide CAS: 68-12-2; 1,4-dioxane CAS: 123-91-1; zirconium nitrate C AS: 13826-66-9; Tetrabutyl titanate CAS: 5593-70-4; Hafnium oxychloride CAS: 13759-17-6; Ethanol CAS: 64-17-5; Strontium nitrate CAS: 10042-76-9; Citric acid CAS: 77-92-9; γ-aminopropyltriethoxysilane CAS: 919-30-2; Tris-HCl buffer solution; Dopamine CAS: 51-61-6; Boric acid CAS: 10043-35-3.

[0044] Example

[0045] Example 1

[0046] An all-vanadium liquid flow battery felt is prepared by pre-oxidation and carbonization of raw silk fibers of perovskite-type metal oxides coated with nitrogen-phosphorus-containing polyacrylonitrile copolymers.

[0047] Specifically, the preparation process of all-vanadium liquid flow battery felt includes the following steps:

[0048] Step 1: Prepare nanofiber membrane by electrospinning the nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with perovskite-type metal oxide. During the spinning process, the spinning solution flow rate is 0.8 ml / h, the receiving distance is 15 cm, the receiving end rotor speed is 600 rpm, the voltage between the needle and the receiving end is 30 kV, the temperature is 30 ° C, the relative humidity is 60%, and the nanofiber membrane thickness is 2 mm;

[0049] Step 2: Place the nanofiber membrane in the air for pre-oxidation. After the pre-oxidation is completed, place it in an argon or nitrogen atmosphere for high-temperature carbonization to obtain an active porous carbon fiber electrode; the pre-oxidation temperature is 25°C, the heating rate is 6°C / min, the time is 2h, and the carbonization temperature is 1300°C, the heating rate is 6°C, and the time is 3h.

[0050] The method for preparing the nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with a perovskite-type metal oxide comprises the following steps:

[0051] S1. First, dispersing pentaerythritol phosphate in N, N-dimethylformamide, then adding 3-isopropenyl-α, α-dimethylbenzyl isocyanate, heating to react, and then precipitating, filtering and drying in deionized water to obtain a nitrogen-phosphorus intermediate;

[0052] The mass ratio of pentaerythritol phosphate to 3-isopropenyl-α, α-dimethylbenzyl isocyanate is 5:12, the reaction temperature is 45°C, the reaction time is 4h, and N,N-dimethylformamide is in excess;

[0053] S2, dispersing the amino perovskite metal oxide in N, N-dimethylformamide, and then adding dicyclohexylcarbodiimide and 2-(carboxymethylthio)benzoic acid, mixing and stirring evenly to obtain a perovskite metal oxide chain transfer agent;

[0054] The mass ratio of amide perovskite metal oxide, 2-(carboxymethylthio)benzoic acid and dicyclohexylcarbodiimide is 1:2:1.5, the reaction temperature is 25°C, and the reaction time is 25h;

[0055] S3, mixing 1,4-dioxane, a perovskite-type metal oxide chain transfer agent, azobisisoheptanenitrile, a nitrogen-phosphorus-containing intermediate and acrylonitrile to obtain a nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with a perovskite-type metal oxide;

[0056] The mass ratio of perovskite metal oxide chain transfer agent, azobisisoheptanenitrile, nitrogen-phosphorus intermediate and acrylonitrile is 0.4:0.2:0.7:10, the reaction temperature is 50°C, and the reaction time is 15h.

[0057] The preparation method of the amination perovskite-type metal oxide is as follows:

[0058] Zirconium oxynitrate is dissolved in deionized water, and then strontium nitrate is added and dissolved completely. In the solution, the molar ratio of strontium to titanium is 1:1. Then, citric acid as a complexing agent is added, and the molar amount of citric acid is 1.5 times the molar amount of total metal ions. Then, the mixture is mixed and stirred at 80°C to form a transparent sol, and then dried and ground into powder. After that, the mixture is calcined at 900°C for 3 hours, and finally, mixed and dried with 20wt% of the total mass of γ-aminopropyltriethoxysilane to obtain an amino perovskite-type metal oxide SrZrO3.

[0059] Example 2-3

[0060] The difference from Example 1 is that in the preparation of the nitrogen-phosphorus-containing polyacrylonitrile copolymer coated perovskite-type metal oxide, the mass proportions of the raw materials in each step are different, as shown in Table 1.

[0061] Table 1 The mass ratio of each raw material in each step of Examples 1-3

[0062]

[0063] Example 4

[0064] The difference from Example 1 is that zirconyl nitrate is replaced by the same amount of tetrabutyl titanate, the tetrabutyl titanate is dissolved in ethanol, and the perovskite metal oxide is SrTiO3.

[0065] Example 5

[0066] The difference from Example 1 is that zirconium oxynitrate is replaced by the same amount of hafnium oxychloride, and the perovskite metal oxide is SrHfO3.

[0067] Example 6

[0068] The difference from Example 1 is that a dopamine-boron system is attached to the surface of the precursor fiber of the nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with the perovskite-type metal oxide;

[0069] The attachment method of the dopamine boron system is:

[0070] First, the raw silk fibers coated with nitrogen and phosphorus-containing polyacrylonitrile copolymers of perovskite-type metal oxides are dried and immersed in Tris-HCl buffer, and dopamine monomer is added and stirred. The oxygen in the air is used as a catalyst to achieve dopamine self-polymerization and coating. The coated raw silk fibers are then immersed in a boric acid solution, and finally washed and dried to complete the attachment of the dopamine boron-boron system.

[0071] The concentration of dopamine monomer added was 2.5 g / L, and the mass ratio of the nitrogen-phosphorus-containing polyacrylonitrile copolymer-coated perovskite-type metal oxide precursor fiber to dopamine was 3.5:2.5;

[0072] The concentration of the boric acid solution is 1-5 g / L, and the mass ratio of the nitrogen-phosphorus-containing polyacrylonitrile copolymer-coated perovskite-type metal oxide precursor fiber to the boric acid is 3.5:3.

[0073] Embodiment 7-8

[0074] The difference from Example 6 is that the mass proportions of the raw material components of the dopamine boron system are different, as shown in Table 2.

[0075] Table 2 The mass ratio of each raw material component of the dopamine boron system in Examples 6-8

[0076]

[0077] Comparative Example

[0078] Comparative Example 1

[0079] A vanadium liquid flow battery felt, the preparation method of which comprises the following steps:

[0080] 1. Add polyacrylonitrile and perovskite metal oxide SrZrO3 to dimethylacetamide, stir and mix evenly in a water bath to obtain an electrospinning solution; the mass ratio of polyacrylonitrile, perovskite metal oxide SrZrO3 and dimethylacetamide is 1:0.4:10, the water bath temperature is 60°C, and the stirring time is 8h;

[0081] 2. The electrospinning solution was electrospun to obtain a nanofiber membrane; during the spinning process, the spinning solution flow rate was 0.8 ml / h, the receiving distance was 15 cm, the receiving end rotor speed was 600 rpm, the voltage between the needle and the receiving end was 30 kV, the temperature was 30 ° C, the relative humidity was 60%, and the nanofiber membrane thickness was 2 mm;

[0082] 3. Place the nanofiber membrane in the air for pre-oxidation. After the pre-oxidation is completed, place it in an argon or nitrogen atmosphere for high-temperature carbonization to obtain an active porous carbon fiber electrode; the pre-oxidation temperature is 25°C, the heating rate is 6°C / min, the time is 2h, and the carbonization temperature is 1300°C, the heating rate is 6°C, and the time is 3h.

[0083] Comparative Example 2

[0084] The difference from Example 1 is that in the preparation method S3 of the nitrogen-phosphorus-containing polyacrylonitrile copolymer-coated perovskite-type metal oxide, no nitrogen-phosphorus-containing intermediate is added.

[0085] Performance testing

[0086] Detection Methods

[0087] 1. Battery Energy Efficiency Test

[0088] Three samples with a size of 2 cm×2 cm were taken out from Examples 1-8 and Comparative Examples 1-2 respectively, and used as electrodes of all-vanadium liquid flow batteries. The electrodes, polytetrafluoroethylene pads, Nafion@NR-212 diaphragms, graphite plates with interdigital flow fields, gold-plated copper current collecting plates, aluminum end plates and bakelite plates were assembled into single cells by fastening with bolts.

[0089] The positive electrolyte is 20 ml 1M VO 2+ +3M H2SO4 solution, negative electrode electrolyte is 20ml 1M V 3+ +3MH2SO4 solution. The electrolyte circulates through a dual-channel peristaltic pump at a pump rate of 77ml / min. The all-vanadium redox flow battery is tested at 200mA / cm 2 Constant current charging and discharging under current density, obtain the energy efficiency of the battery and take the average value.

[0090] The test data are shown in Table 3.

[0091] 2. Long-term stability test

[0092] Three samples were taken out from Example 1 and Comparative Example 1 respectively. The samples were stored for 3 years. The sample specifications were 2cm×2cm. They were used as electrodes of all-vanadium liquid flow batteries. The electrodes, polytetrafluoroethylene pads, Nafion@NR-212 diaphragms, graphite plates with interdigital flow fields, gold-plated copper current collecting plates, aluminum end plates and bakelite boards were assembled into single cells by bolting.

[0093] The positive electrolyte is 20 ml 1M VO 2+ +3M H2SO4 solution, negative electrode electrolyte is 20ml 1M V 3+ +3MH2SO4 solution. The electrolyte circulates through a dual-channel peristaltic pump at a pump rate of 77ml / min. The all-vanadium redox flow battery is tested at 200mA / cm 2 Constant current charging and discharging under current density, obtain the energy efficiency of the battery and take the average value, and finally calculate the loss value.

[0094] Loss value = battery energy efficiency - battery energy efficiency after 3 years.

[0095] The test data are shown in Table 4.

[0096] Table 3 Battery energy efficiency table of Examples 1-8 and Comparative Examples 1-2 (%)

[0097]

[0098] Table 4 Loss values ​​obtained in Example 1 and Comparative Example 1 / %

[0099]

[0100] With reference to Example 1 and Comparative Examples 1-2 and in combination with Tables 3-4, it can be seen that, relative to Comparative Example 1, the battery energy efficiency of Example 1 and Comparative Example 2 is significantly improved, and the damage value of Example 1 and Comparative Example 2 is also significantly reduced, which indicates that the all-vanadium liquid flow battery felt of the present application has excellent electrochemical activity, and the perovskite-type metal oxide can exist on the surface of the carbon fiber for a long time.

[0101] The reason is that, in the synthesis, the hydroxyl group of pentaerythritol phosphate reacts with 3-isopropenyl-α, α-dimethylbenzyl isocyanate to obtain a phosphorus-nitrogen-containing vinyl monomer, and the amino perovskite-type metal oxide reacts with 2-(carboxymethylthio)benzoic acid through an amide reaction to synthesize a grafted chain transfer agent, which, under the initiation of azobisisoheptanenitrile, promotes the polymerization of the phosphorus-nitrogen-containing vinyl monomer and acrylonitrile on the surface of the perovskite-type metal oxide chain transfer agent, thereby completing the loading of phosphorus and nitrogen while also coating the perovskite-type metal oxide, promoting the perovskite-type metal oxide to be coated inside the nitrogen-phosphorus polyacrylonitrile copolymer, thereby effectively reducing the possibility of the perovskite-type metal oxide detaching from the fiber, and indirectly improving the electrochemical activity of the all-vanadium liquid flow battery felt.

[0102] Referring to Examples 1-3 and in combination with Table 3, it can be seen that relative to Example 1, the battery energy efficiency of Examples 2-3 is slightly reduced. This indicates that in the preparation of nitrogen-phosphorus-containing polyacrylonitrile copolymer-coated perovskite-type metal oxide, when the raw materials in each step adopt the mass proportion of Example 1, the prepared all-vanadium liquid flow battery felt will have better electrochemical activity.

[0103] With reference to Example 1 and Examples 4-5 and in combination with Table 3, it can be seen that the battery energy efficiency of Examples 4-5 is slightly reduced compared with that of Example 1. This indicates that when SrZrO3 is used as the perovskite metal oxide, the all-vanadium liquid flow battery felt has better electrochemical activity than when SrTiO3 or SrHfO3 is used as the perovskite metal oxide.

[0104] The reason is that SrZrO3 has relatively more oxygen defects, which promotes the adsorption of vanadium ions. At the same time, the Zr-O bond orbital hybridization is weak, which is conducive to the charge transfer of the anode reaction. At the same time, SrZrO3 has good hydrophilicity, large surface area, excellent crystal structure and relatively moderate particle size, which ensures excellent catalytic activity.

[0105] Referring to Example 1 and Example 6 and combining with Table 3, it can be seen that compared with Example 1, the battery energy efficiency of Example 6 is further improved, which shows that the setting of the dopamine boron system can further improve the electrochemical activity of the all-vanadium liquid flow battery felt.

[0106] The reason is that the attachment of the dopamine-boron system promotes the simultaneous doping of boron on the surface of the carbon fiber, and boron can form pn-type co-doping with P and N. Specifically, pn co-doping is the co-doping of n-type atoms with lone pairs of electrons and p-type atoms with empty orbitals into the electrode, wherein N and P can introduce defects and vacancies in the carbon matrix, thereby serving as new active sites to accelerate the redox reaction of vanadium ions, and B can form transition bonds with vanadium ions, thereby promoting electron transfer between reactants and electrodes, thereby increasing the hydrophilicity of the electrode while increasing the active sites.

[0107] Referring to Examples 6-8 and in combination with Table 3, it can be seen that the electrochemical activity of Examples 7-8 is slightly reduced compared to that of Example 6. This indicates that when the raw material components of the dopamine boron system adopt the mass proportions of Example 6, the prepared all-vanadium liquid flow battery felt will have better electrochemical activity.

[0108] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An all-vanadium liquid flow battery felt, characterized in that: The all-vanadium liquid flow battery felt is prepared by pre-oxidation and carbonization of raw silk fibers of perovskite-type metal oxides coated with nitrogen-phosphorus-containing polyacrylonitrile copolymers; The dopamine-boron system is attached to the surface of the precursor fiber of the nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with the perovskite-type metal oxide; The attachment method of the dopamine boron system is: First, the raw silk fibers coated with nitrogen and phosphorus-containing polyacrylonitrile copolymers of perovskite-type metal oxides are dried and immersed in Tris-HCl buffer, and dopamine monomer is added and stirred. The oxygen in the air is used as a catalyst to achieve dopamine self-polymerization and coating. The coated raw silk fibers are then immersed in a boric acid solution, and finally washed and dried to complete the attachment of the dopamine boron-boron system.

2. The all-vanadium liquid flow battery felt according to claim 1, characterized in that: The nitrogen-phosphorus-containing polyacrylonitrile copolymer coated perovskite-type metal oxide comprises the following raw materials: pentaerythritol phosphate, 3-isopropenyl-α, α-dimethylbenzyl isocyanate, amide perovskite-type metal oxide, dicyclohexylcarbodiimide, 2-(carboxymethylthio)benzoic acid and azobisisoheptonitrile.

3. The all-vanadium liquid flow battery felt according to claim 2, characterized in that: The method for preparing the nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with a perovskite-type metal oxide comprises the following steps: S1. First, dispersing pentaerythritol phosphate in N, N-dimethylformamide, then adding 3-isopropenyl-α, α-dimethylbenzyl isocyanate, heating to react, and then precipitating, filtering and drying in deionized water to obtain a nitrogen-phosphorus intermediate; S2, dispersing the amino perovskite metal oxide in N, N-dimethylformamide, and then adding dicyclohexylcarbodiimide and 2-(carboxymethylthio)benzoic acid, mixing and stirring evenly to obtain a perovskite metal oxide chain transfer agent; S3, mixing 1,4-dioxane, a perovskite-type metal oxide chain transfer agent, azobisisoheptylnitrile, a nitrogen-phosphorus-containing intermediate and acrylonitrile to obtain a nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with a perovskite-type metal oxide.

4. The all-vanadium liquid flow battery felt according to claim 3, characterized in that: In S1, the mass ratio of pentaerythritol phosphate to 3-isopropenyl-α, α-dimethylbenzyl isocyanate is (3-6): (10-14), the reaction temperature is 40-50°C, and the reaction time is 3-5h; and / or; In S2, the mass ratio of the amide perovskite-type metal oxide, 2-(carboxymethylthio)benzoic acid and dicyclohexylcarbodiimide is 1:(1-3):(1-2), the reaction temperature is 20-30°C, and the reaction time is 20-30h; and / or; In S3, the mass ratio of the perovskite-type metal oxide chain transfer agent, azobisisoheptanenitrile, nitrogen-phosphorus intermediate and acrylonitrile is (0.2-0.5): (0.15-0.25): (0.5-0.8): (8-12), the reaction temperature is 40-60°C, and the reaction time is 10-20h.

5. The all-vanadium liquid flow battery felt according to claim 1, characterized in that: The structural formula of the perovskite metal oxide is ABO3, A is one of Ca, Sr and Ba, and B is one of Ti, Zr and Hf.

6. The all-vanadium liquid flow battery felt according to claim 5, characterized in that: The perovskite metal oxide is SrZrO3.

7. The all-vanadium liquid flow battery felt according to claim 2, characterized in that: The preparation method of the amination perovskite-type metal oxide is: Zirconium oxynitrate is dissolved in deionized water, and then strontium nitrate is added and dissolved completely. In the solution, the molar ratio of strontium to titanium is 1:

1. Then, citric acid as a complexing agent is added, and the molar amount of citric acid is 1.5 times the molar amount of total metal ions. Then, the mixture is mixed and stirred at a temperature of 70-90°C to form a transparent sol, and then dried and ground into powder. After that, the mixture is calcined at a temperature of 800-1000°C for 2-4h, and finally mixed and dried with 20wt% of the total mass of γ-aminopropyltriethoxysilane to obtain an amino perovskite metal oxide SrZrO3.

8. The all-vanadium liquid flow battery felt according to claim 1, characterized in that: The dopamine monomer is added at a concentration of 1-4 g / L, and the mass ratio of the nitrogen-phosphorus-containing polyacrylonitrile copolymer-coated perovskite-type metal oxide precursor fiber to dopamine is (2-5): (1-4); The concentration of the boric acid solution is 1-5 g / L, and the mass ratio of the nitrogen-phosphorus-containing polyacrylonitrile copolymer-coated perovskite-type metal oxide precursor fiber to boric acid is (2-5): (1-5).

9. A process for preparing the all-vanadium liquid flow battery felt according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Prepare a nanofiber membrane by electrospinning a nitrogen-phosphorus-containing polyacrylonitrile copolymer coated with a perovskite-type metal oxide. During the spinning process, the spinning solution flow rate is 0.5-1.0 ml / h, the receiving distance is 10-20 cm, the receiving end rotor speed is 500-800 rpm, the voltage between the needle and the receiving end is 20-40 kV, the temperature is 20-40 ° C, the relative humidity is 40-70%, and the nanofiber membrane thickness is 1-3 mm; Step 2: Place the nanofiber membrane in the air for pre-oxidation, and then place it in an argon or nitrogen atmosphere for high-temperature carbonization to obtain an active porous carbon fiber electrode; the pre-oxidation temperature is 200-300°C, the heating rate is 2-8°C / min, the time is 1-3h, and the carbonization temperature is 800-3000°C, the heating rate is 4-10°C, and the time is 2-4h.